The Effects of COVID-19-related Driving Restrictions on Air Quality in an Industrial City - Daulet Assanov; Aiymgul Kerimray; Birzhan Batkeyev; Zhanna Kapsalyamova (Aerosol and Air Quality Research)
Abstract To slow the spread of COVID-19, the state of emergency was announced in Kazakhstan on March 16, 2020. Ust-Kamenogorsk instituted COVID-19 lockdown measures on April 2, 2020. The restrictions reduced the flow of traffic in the city but did not have a major impact on the large industries and power plants. In the areas with a complex profile of emission sources, traffic restriction measures alone may hardly tackle serious air pollution. This natural experiment allowed us to test how the reduction in transport movement affects air quality in Ust-Kamenogorsk, as there is a tendency to hold transport as being a major cause of air pollution in Ust-Kamenogorsk. This study analyzes concentrations of four major air pollutants and meteorological parameters in Ust-Kamenogorsk from March 1 to May 15 in 2016–2020. Using the fixed effects model, we find that restrictions have decreased the levels of CO by 21–23 percent, increased the levels of TSP by 13–21 percent, and had no significant effect on SO2 and NO2 concentrations in the city. It implies that heavy pollution in the city with SO2, NO2, TSP are mainly caused by non-transport-related sources.